An educational model for preparing Christian nurses and church congregations to offer local whole-person health programmes - Helen Anne Wordsworth (Health for All Nations, 2016)
The implications of the Tübingen declarations for congregational involvement in health provide the setting for this commentary. Using an example from the United Kingdom, where government health provision has become economically challenging and largely disease focused, the author demonstrates how it is possible to introduce the kind of education for nurses and congregations that will lead to them becoming important sources of whole-person health promotion. In this way, parish nurses and church congregations may make a distinctive contribution that will complement state and private health provision. This model has relevance across all Christian denominations. It is already being followed in 28 different countries, and with appropriate respect to culture, language and health policy, could be globally transferable.